2011
DOI: 10.1021/ac1033209
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Acquisition of Elemental, Fragmental, and Molecular Information on Organometallic Compounds

Abstract: A novel method for obtaining elemental, fragmental, and molecular information of organometallic compounds has been developed using high irradiance laser induced time-of-flight mass spectrometry (LI-TOFMS) with a buffer-gas-assisted ion source. This technique permits direct and matrix-free analysis of solid analyte with minimal sample preparation. In addition, it shows special advantages in integrated acquisition of elemental, fragmental, and molecular information from a single target, on the basis of which ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…They reported several examples of LIMS analysis of solid organic compounds performed with minimal sample preparation. Study of two low molecular weight metalloorganic compounds (benzoylferrocene and nickel acetylacetonate), which were pressed into solid discs and then ionized, demonstrated the possibility to influence the ionization and fragmentation processes by the adjustment of the buffer gas (He) pressure (Yu et al, 2011). The authors reported that at lower buffer gas pressures of 50-100 Pa intact molecules and relatively low fragmentation were observed in MS spectra, whereas the increase of the pressure led to more extensive fragmentation and, finally, only heavy metal ions (Fe + and Ni + , respectively) were detected in MS spectra at pressures of 1000-1500 Pa.…”
Section: Use Of Lims In Analysis Of Organic and Biological Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported several examples of LIMS analysis of solid organic compounds performed with minimal sample preparation. Study of two low molecular weight metalloorganic compounds (benzoylferrocene and nickel acetylacetonate), which were pressed into solid discs and then ionized, demonstrated the possibility to influence the ionization and fragmentation processes by the adjustment of the buffer gas (He) pressure (Yu et al, 2011). The authors reported that at lower buffer gas pressures of 50-100 Pa intact molecules and relatively low fragmentation were observed in MS spectra, whereas the increase of the pressure led to more extensive fragmentation and, finally, only heavy metal ions (Fe + and Ni + , respectively) were detected in MS spectra at pressures of 1000-1500 Pa.…”
Section: Use Of Lims In Analysis Of Organic and Biological Samplesmentioning
confidence: 99%
“…Because of that, they cannot ionize the molecules desorbed from the surface by the thermal diffusion, and only small fragment ions are observed in the MS spectra. In the case of metalloorganic compounds these were exclusively heavy metal ions (Yin et al 2014b(Yin et al , 2014aYu et al, 2011). At low buffer gas pressures, electrons, protons, and ions have much longer mean free paths leading to numerous collisions with thermaldesorbed molecules, from which parent radicals are generated.…”
Section: Use Of Lims In Analysis Of Organic and Biological Samplesmentioning
confidence: 99%
“…Laser ionization mass spectrometry is an increasingly popular method of elemental and isotopic analysis, and a number of reviews were recently published. [1][2][3] Several advantages of laser ionization time-of-flight mass spectrometry allow one to apply the method for semiquantitative multielemental analysis of both organic and unorganic samples. [4][5][6][7][8] Modeling of mass analyzers is the first stage of timeof-flight mass spectrometers design process.…”
Section: Introductionmentioning
confidence: 99%
“…Laser ionization orthogonal TOF mass spectrometry was applied to simultaneous determination of nonmetallic elements in solids, 35 semi-quantitative multielement analysis of biological samples, 36 the elemental analysis of residues, which were prepared by evaporating mixed salt solutions, 37 obtaining elemental, fragmental, and molecular information of organometallic compounds, 38 and semi-quantitative analysis of geological samples. 39 Femtosecond laser ablation TOF mass spectrometry was shown to be very efficient in direct sampling elemental analysis of solids.…”
Section: Introductionmentioning
confidence: 99%